Examining the influencing factors and the functioning mechanism of online learning supporting learners’ empowerment - Pan, Xiaoquan (Frontiers in Psychology, 2022)
The construction of an effective technology-based environment to promote learning and enable online learning to truly empower learners has become an increasingly important issue of concern. To some extent, an in-depth analysis of the key influencing factors and their functioning mechanism of online learning supporting learners’ empowerment may pave a new way for the understanding of this issue. In view of this, this study, grounded on the reciprocal determinism theory, explored the influencing paths among environment elements, online behaviors, person factors and learners’ empowerment by using structural equation modeling (SEM) approach, and examined the structure effect relationships among these dimensions. A total of 396 Chinese university students reported on their perceptions of environment elements, online behaviors, person factors, and learners’ empowerment through the questionnaire survey. The results showed that there was a strong correlation between the three dimensions of the reciprocal determinism theory, and the three dimensions all exerted a positive effect on learners’ empowerment. Among them, the item parameter estimates revealed that online environment, online interaction and online cooperation were significant in explaining the influence of environment elements and online behaviors on learners’ empowerment. Based on the empirical results, this study provided some implications and suggestions for the rationality of the structure devising of online learning environment, the effectiveness of online teacher-student interaction and the development of students’ learning autonomy in technology-based learning. Thus, this study helped understand the specific contribution of external and internal factors to learners’ empowerment of using technology for online learning and would inform the construction of the optimized online learning environments and teacher-student relationships to enhance students’ sense of online presence and learning initiative.